MATHEMATICAL MODELING OF THE START-UP SEQUENCE OF A WASTEWATER TREATMENT SYSTEM: INTEGRATION OF PHYSICOCHEMICAL PROCESSES - Gafurova Mexrnoz Odiljonovna (Modern American Journals, 2025)
The article examines how the time- and energy-intensive stage of reagent-based treatment of industrial wastewater can be eliminated by introducing a wastewater treatment device operating in an electromagnetic field. The operational sequence of the device, the algorithm developed for its functioning, and the corresponding results are presented.
Keywords: Industrial wastewater, substance removal efficiency, pipeline, water parameters, energy and resource consumption, mass balance.